2020
DOI: 10.5811/westjem.2020.1.45279
|View full text |Cite
|
Sign up to set email alerts
|

Using Tenecteplase for Acute Ischemic Stroke: What Is the Hold Up?

Abstract: Alteplase is the only Food and Drug Administration-approved intravenous (IV) thrombolytic medication for acute ischemic stroke. However, multiple recent studies comparing tenecteplase and alteplase suggest that tenecteplase is at least as efficacious as alteplase with regards to neurologic improvement. When given at 0.25 milligrams per kilogram (mg/kg), tenecteplase may have less bleeding complications than alteplase as well. This narrative review evaluates the literature and addresses the practical issues wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 21 publications
(37 reference statements)
0
15
0
2
Order By: Relevance
“…79,[81][82][83] Although alteplase is currently the only FDA-approved tPA medication for AIS, its administration increases the patient's risk of intracranial haemorrhage. 84 Although not FDA-approved for acute stroke, studies have shown that tenecteplase has both a greater fibrin specificity and longer half-life compared to alteplase, resulting in greater reperfusion on imaging studies and superior clinical neurological outcomes at 24 hours. 85,86 However, the benefits of bridging therapy with intravenous thrombolysis remain unclear according to the SKIP studies; this meta-analysis questions the additional benefits of the use of thrombolysis before thrombectomy.…”
Section: Thrombus Composition and Thrombolytic Therapymentioning
confidence: 99%
“…79,[81][82][83] Although alteplase is currently the only FDA-approved tPA medication for AIS, its administration increases the patient's risk of intracranial haemorrhage. 84 Although not FDA-approved for acute stroke, studies have shown that tenecteplase has both a greater fibrin specificity and longer half-life compared to alteplase, resulting in greater reperfusion on imaging studies and superior clinical neurological outcomes at 24 hours. 85,86 However, the benefits of bridging therapy with intravenous thrombolysis remain unclear according to the SKIP studies; this meta-analysis questions the additional benefits of the use of thrombolysis before thrombectomy.…”
Section: Thrombus Composition and Thrombolytic Therapymentioning
confidence: 99%
“…Tenecteplase is also currently cheaper. A 50 mg vial of tenecteplase costs approximately $6300 while a 100 mg vial of alteplase costs approximately $9200 [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to the EXTEND-IA TNK trial, similar non-inferior primary and secondary outcomes were also observed when patients with mainly large vessel occlusions and major neurological deficits were included 31 . If other factors such as ease of administration and cost were also taken into account 33 , it makes for a strong case that TNK should be used over alteplase for thrombolysis in ischemic strokes. Perhaps the reluctance to initiate TNK stems from the uncertainty revolving the optimal dose and timing of administration of TNK, which saw a significant degree of heterogeneity in a published meta-analysis conducted 32 .…”
Section: R I P Tmentioning
confidence: 99%